Pengaruh Produk Domestik Regional Bruto, Tingkat Partisipasi Angkatan Kerja Dan Kemiskinan Terhadap Indeks Pembangunan Manusia di Provinsi Kalimantan Selatan Tahun 2011-2020 - Hafifah, Noor; Suherty, Lina (PPJP ULM, 2023)
The basis of this study is to (1) analyze the effect of the variables GRDP, Labor Force Participation, and Poverty partially and simultaneously in South Kalimantan Province for the 2011-2020 period and (2) to analyze which factors are more dominant in influencing the Human Development Index in South Kalimantan Province in the period 2011-2020. This type of research is quantitative, while the analysis technique used is multiple linear regression analysis with time series using Eview 9. The results of this study indicate that GRDP partially affects the Human Development Index significantly, and LFPR and Poverty do not partially affect the Human Development Index. The three independent variables simultaneously significantly affect the Human Development Index in South Kalimantan Province. The most significant influence on the Human Development Index is the GRDP variable.